Evaluating the impact of post - emergence weed control in honeybee colonies located in different agricultural surroundings - Macri, Ivana N. (2021)
Fil: Macri, Ivana N. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Biodiversidad y Biología Experimental. Buenos Aires, Argentina.